Chemical Composition, Antioxidant and Antibacterial Activities of Leaves Essential Oil and Ethanolic Extract of Moroccan Warionia saharae Benth. & Coss. - F. Amezouar, W. Badri, M. Hsaine, N. Bourhim, H. Fougrach (Journal of Applied Pharmaceutical Science)
The aims of this study were to analyze the chemical composition of leaves essential oil of Warionia saharae, to evaluate the antioxidant capacity (DPPH test), antibacterial properties and to investigate toxicity against Artemia salina of both oil and ethanolic extract. The results showed that essential oil was toxic (CL50 = 1,56 µg/ml). The GC–MS analysis revealed 52 compounds representing 91.54% of the total oil containing Nerolidol (25,95%) and ß-Eudesmol (38,12%) as a major components. The oil (1 mg/ml) exhibited a strong antibacterial effect as a diameter of zones of inhibition (28,5 ± 2,12 and 37,5 ± 3.53 mm) against St. aureus and P. aeruginosa, respectively. While, ethanolic extract (50 mg/ml) exhibited a moderate effect against all tested bacterial strains. MICs values of oil and the extract were ranged 0,031-0,25 µg/ml and 6,25-12,5 mg/ml, respectively. The free radical scavenging activities of the oil was higher than that of ethanolic extract (IC50 = 21,49 and IC50 = 182 µg/ml, respectively).
Keywords: Warionia saharae, antioxidant activity,antibacterial activity, CG-MS, ethanolic extract, Artemia salina.